Bioengineering Approaches for Nanomedicine Delivery in Therapy of Myocardial Infarction - Jiawen Zou; Dashuai Zhu; Xiao Cheng; Ke Cheng (Arteriosclerosis, Thrombosis, and Vascular Biology, 2026)
Cardiovascular disease remains the leading cause of death globally. In particular, ischemic heart disease represents the most common condition in clinics. Adult hearts have minimal regenerative capacity. Upon myocardial infarction, the formation of activated myofibroblasts replaces the massive loss of cardiomyocytes. Nanomedicine has emerged as a promising strategy for cardiovascular disease treatment, with synthetic nanoparticles and extracellular vesicles serving as representative delivery platforms. However, directly applying these nanomedicines faces several challenges, including insufficient cardiac targeting, poor retention rate at the injured site, and potential biocompatibility concerns. To overcome these limitations, different bioengineering approaches have been adopted. In this review, we discussed the landscape of cardiovascular nanomedicine, encompassing both synthetic nanocarriers and biological carriers and targeted delivery. We further evaluated the engineering approaches to enhance carrier performance. Multiple administration routes are also compared. Collectively, these advances represent a shift toward an integrated, multifunctional delivery platform with the potential to translate cardiac nanomedicine from bench to bedside.